Perubahan Tari Makan Sirih Ke Tari Persembahan Melayu Riau Di Kota Pekanbaru Provinsi Riau - Cut Bunga Maharani Nazlen; Darmawati Darmawati (FBS Universitas Negeri Padang, 2022)
This study aims to analyze the changes in the Riau Makan Sirih Melayu Dance which are focused on changing the form of the dance. This type of research is qualitative research with a descriptive analysis method with the object of research namely Riau Malay dance. The main instrument of this research is the researcher himself making direct observations in the field and assisted by supporting instruments such as; stationery, digital cameras, tape recorders, CD cassettes, and flash drives. Data collection techniques were carried out through literature study, observation, interviews, and documentation. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions. The results showed that the change of the Makan Sirih Dance into the Riau Persembahan Melayu Dance consisted of a change in the name and the form of presentation.